The Impact of the Four Modernization Program on the Development of China`s Position in the International System: (1978-2020) (The International Journal for Scientific Research, 2024)
The study aims to identify the details and stages of the program The four modernization adopted by China in 1978, It also aims to demonstrate its importance and its results, while supporting the study with comparative statistical tables through which it can be inferred on the impact of this program on Chinese economic development, and the extent of China's ability to employ its economic success in enhancing its role and effectiveness in the international system. The researcher used the historical method to identify the development of the Chinese state for different historical stages, and the descriptive method collects facts and information, analyzes and interprets the phenomenon through which it defines its characteristics and dimensions and describes the relationship between them in order to reach an integrated scientific description.The study concluded that one of the most important factors for China's development and economic success is its import of advanced Western technology, its attraction of international investments, and the presence of global markets to export its products, especially the American market, which forced it to avoid any confrontation or escalation with the United States of America in particular. Finally, the success of the four modernization program in the development of China's position in the international system, especially in the economic field, imposed on China to move forward in developing its military system, relying on quality, not quantity, and considering the military system not to protect borders only, but also as a catalyst for economic development, infrastructure support, protection and ensuring the smooth flow of movement Chinese interests extending across the world.
Keywords: Development of China's Position; the Four Modernization Program; the International System